Political economy of growth regimes in Poland and Turkey - Ümit Akcay; Benjamin Jungmann (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2022)
In this paper, we aim to contribute to the recently growing body of political economy literature on growth regimes. Theoretically, we apply the demand and growth regime approach developed within post-Keynesian macroeconomics. This is complemented by a critical comparative political economy perspective to analyse the socio-political underpinnings of a demand and growth regime by using the concept of dominant social blocs and their growth strategies. We posit that the concept of growth strategy is useful to uncover the intention of a dominant social bloc to consolidate or change the current demand and growth regime. Using this framework, we examine the demand and growth regimes of Poland and Turkey from 1999 to 2020. We identify a domestic demand-led regime in Poland between 1999 and 2008, which transitioned to a weakly export-led regime between 2009 and 2020. In Turkey, we identify a domestic demand-led regime before the Global Financial Crisis (GFC) that became a private debt-led regime until the taper tantrum in 2013. Since then, a development towards a more export-led regime is observable, albeit at lower and unstable growth levels. We argue that in both countries the trend toward a more export-led regime after the GFC is associated to changes in the dominant social blocs. Both of the new dominant social blocs that established themselves during the 2010s - represented by the PiS-party in Poland and the AKP in Turkey - pursue a growth strategy toward "national capitalism". Politically, these strategies have come with a democratic backlash. Economically, they aim to gain more control over key sectors such as banking and finance while developing a more competitive export sector through domestic re-industrialisation initiatives.
Keywords: B52; E65; E66; F43; O43; P16; P52; 330; Post-Keynesian macroeconomics; comparative political economy; growth regimes; growth strategies; Poland; Turkey